Discovery of long non-coding RNAs in the liver fluke, Fasciola hepatica. - Paul McVeigh; Erin McCammick; Emily Robb; Peter Brophy; Russell M Morphew; Nikki J Marks; Aaron G Maule (PLoS Neglected Tropical Diseases, 2023)
Long non-coding (lnc)RNAs are a class of eukaryotic RNA that do not code for protein and are linked with transcriptional regulation, amongst a myriad of other functions. Using a custom in silico pipeline we have identified 6,436 putative lncRNA transcripts in the liver fluke parasite, Fasciola hepatica, none of which are conserved with those previously described from Schistosoma mansoni. F. hepatica lncRNAs were distinct from F. hepatica mRNAs in transcript length, coding probability, exon/intron composition, expression patterns, and genome distribution. RNA-Seq and digital droplet PCR measurements demonstrated developmentally regulated expression of lncRNAs between intra-mammalian life stages; a similar proportion of lncRNAs (14.2%) and mRNAs (12.8%) were differentially expressed (p<0.001), supporting a functional role for lncRNAs in F. hepatica life stages. While most lncRNAs (81%) were intergenic, we identified some that overlapped protein coding loci in antisense (13%) or intronic (6%) configurations. We found no unequivocal evidence for correlated developmental expression within positionally correlated lncRNA:mRNA pairs, but global co-expression analysis identified five lncRNA that were inversely co-regulated with 89 mRNAs, including a large number of functionally essential proteases. The presence of micro (mi)RNA binding sites in 3135 lncRNAs indicates the potential for miRNA-based post-transcriptional regulation of lncRNA, and/or their function as competing endogenous (ce)RNAs. The same annotation pipeline identified 24,141 putative lncRNAs in F. gigantica. This first description of lncRNAs in F. hepatica provides an avenue to future functional and comparative genomics studies that will provide a new perspective on a poorly understood aspect of parasite biology.